Efforts to Improve Mudharabah Finance of Sharia Commercial Banks through Third Party Funds and Return on Asset - Adetia Azmi Tanjung; Hajar Affiah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The main focus of this study is to analyze the effect of both partial and simultaneous third party funds and return on assets on mudharabah financing at Islamic Commercial Banks. The approach used in this study is a quantitative approach, because the data measurement uses a numerical scale (numbers). The population and sample in this study are the financial statements of Islamic Commercial Banks containing third party funds, return on assets and mudharabah financing. The years 2016 to 2019 were chosen as the sample for this study. The results showed that partially only third party funds had a positive and significant effect on mudharabah financing, while return on assets had no effect. Then simultaneously the two variables of third party funds and return on assets have a positive and significant effect on mudharabah financing at Islamic Commercial Banks.